KONFLIK BATIN TOKOH NAGISA DALAM ANIME KANOJO MO KANOJO KARYA HIROYUKI - Wayan Putra Mahardika; Ni Luh Gede Meilantari (Program Studi Sastra Jepang Fakultas Bahasa Asing Unmas Denpasar, 2024)
The research purpose is to descibe and examine the inner conflict contained in the character Nagisa in the anime Kanojo mo Kanojo. This research is descriptive qualitative and use the data source from the anime Kanojo mo Kanojo. The data that has been obtained is then analyzed using the theory of personality psychology by Carl Gustav Jung. The research method used in this research is the method of listening and recording, namely by looking for data and recording any inner conflicts experienced by Nagisa character. The results of this study show that Nagisa character experiences inner conflicts that are analyzed using three types of human psychology, namely introvert feeling, introvert intuition, and introvert thinking.